Signal Coordination Analysis Between Intersection: Case Study - Muhammad Abi Berkah Nadi; Achmad Vicky Rumandanu; Ahmad Yudi; Siska Apriwelni; Nurwanda Sari; Meutia Nadia Karunia (Newinera Publisher, 2026)
The increase number of vehicles every year has caused a declining road function and performance, which then causes a high volume of vehicles in Intersection I of Endro Suratmin street – Pulau Tegal street / Pulau Legundi street, Intersection II of Urip Sumoharjo street – Soekarno-Hatta street, and Intersection III of Urip Sumoharjo street – Arif Rahman Hakim street. The distance between intersection I to II is 460 m, and Intersection II to III is 700 m. The distance between these intersections become a factor that lead to unsatisfactory level of comfort for road users, which in turn causes problems. The problem occurs because of the absence of signal coordination between the three intersections which causes traffic jams during peak hours. Therefore, this research will provide alternative solutions to overcome these problems. This research uses data from field surveys including traffic volume, intersection geometry, and traffic signal data. VISSIM software is used to analyze queue lengths and delays in existing conditions and signal coordination planning. In addition, reference methods such as the calculation of the Indonesian Road Capacity Manual, the Webster Method, and the Transportation Research Board in Highway Capacity Manual are also used. As the result of the analysis, it was found that the performance of the three intersections had not been coordinated. In the existing condition, the service level value in each arm reached E service level, only a few arms at the three intersections have C service level with a delay time of 29.58 seconds/vehicle. Therefore, three planning solutions were conducted to coordinate signals between the three intersections using a plan with a new cycle time acquired from the Webster method. Plan I coordinates the signals of the three intersections by using the new cycle time of intersection I at each intersection, Plan II coordinates the signals of the three intersections by using a new cycle time of intersection II at each intersection, and Plan III coordinates the signals of the three intersections in each arms using the new cycle time. Out of the three plans, the first plan is obtained as the best solution for giving a significant reduction in delays with an average service level of B.